(untitled) (Nóema, 2017)
The problem of inner time-consciousness is often defined by Husserl as «the most difficult» one in all of phenomenology. Notably, Husserl does not deal with it in the Logical Investigations and explicitly addresses it only beginning in the early years of the 20th century. This paper investigates the early phase of Husserl’s reflections on time: in particular, it focuses on the notion of «memory» as it is presented in his text on The Phenomenology of Internal Time-Consciousness (1893-1917). As I will show, in these early reflections, Husserl explores three models for thinking about memory and the relation to the past that they establish. 1) First, Husserl embraces a so-called «image theory of memory»: he thinks of the content of an act of recollection as something like an image of the past and conceives of its relation to the corresponding perceptual act in terms of «similarity». 2) After having abandoned this model, he begins conceiving of memory in terms of the distinction Auffassung/Auffassungsinhalt: according to this model, memory and perception share the same content, which is apprehended in two different ways. 3) Husserl later abandons this model and moves toward a conception of the past as an original “mode of givenness”. In outlining these three models, I will draw particular attention to the way Husserl conceives of the «identity» of a memory: how should we understand the relation between memory and the experience of which the memory is made? Is there a correspondence between the two? As I will show, the difficulties in think this «identity» will lead Husserl – even in this early stage of his reflections – toward what Rudolf Bernet has defined as an inversion of the “foundational relation” between memory and experience.